Pre-slaughter factors associated with severe bruising in different primary commercial cuts of bovine carcasses - Garcia, Javier Alexander; Vaz, Ricardo; Vaz, Fabiano; Restle, João; Mendonça, Fábio (Revista Ciência Agronômica, 2019)
The incidence of bruising in bovine carcases is a consequence of several potentially stressful and aggressive factors to which the animals are subjected during pre-slaughter handling. The aim of this study was to identify pre-slaughter factors associated with the severe bruising in different regions of the bovine carcass. The study evaluated 5,028 batches of slaughtered cattle from 154,100 animals. The carcases were analysed for gender, handling on the farm, condition of farm infrastructure, type of truck, distance and journey time from the farm to the slaughterhouse, loading density and time of year in which the animals were slaughtered. The results showed that the sidecut and forequarter are the areas most affected by bruising, with females being the most vulnerable. Loading densities above excess of 401 kg m-2 cause an increase in the number of bruises. The use of larger vehicles results in an increase in bruising, as does the use of poor farming facilities. A decrease in the number of bruises was seen for journey times of more than three hours. All the variables under evaluation are potential causes of injury to bovine carcases. As such, improving the handling conditions and facilities for loading cattle, as well as reducing the stress of transport, are factors which determine a smaller number of bruises in bovine carcases.